Implementasi Akad Wadi’ah Sebagai Perwakilan Agensi Produk Simpanan Pada BPRS Bhakti Sumekar Sumenep - Riskiyah Riskiyah; Sudianto Sudianto (IQTISADIE: Journal of Islamic Banking and Shariah Economy, 2023)
Basically Wadi'ah yad dhamanah'ah at the bank of the company, can manage the money. Wadi’ah yad dhamanah at BPRS Bhakti Sumekar Sumenep manages the savings money from that story to be used in certain economic activities. One of the benefits of opening Wadi'ah yad dhamanah's savings will be to receive a competitive monthly savings bonus according to BPRS Bhakti Sumekar policy. Where, in this case, making the savings product more profitable than the other banks, so fate would be more profitable if saving in BPRS Bhakti Sumekar Sumenep. The purpose of this research is to find out how the implementation of the Wadi'ah yad dhamanah akad on BPRS Bhakti Sumekar Sumenep, and to find out the leverage factor of the Wadi'ah yad dhamanah akad on BPRS Bhakti Sumekar Sumenep. Research uses descriptive qualitative research using observation methods, interviews and documentation that are then analysed to obtain accurate data or information. This research subject was taken from some active officials in BPRS Bhakti Sumekar Sumenep, for the validity of the research data using triangulation. The result of this research is the implementation of Wadi'ah yad dhamanah at BPRS Bhakti Sumekar Sumenep acting as the manager of the funds and the fortune as the owner of the capital, carrying out business with caution and also wisdom and good faith in running financing and investment that is not contrary to the corporate principle, While the environmental and psychological factors are some of the drivers of the use of Wadi’ah yad dhamanah akad at BPRS Bhakti Sumekar Bank.